When gender equality values don’t translate into action - Valcour, Monique (Henry Stewart Talks, 2018)
Through consideration of Laser Consulting (not the company’s real name), this case study explores the relationship between a company’s stated values and its behaviour. If this relationship is not harmonious in practice, senior leadership should work to assure a fit between stated values and actual company practices.